PENJUALAN SERAGAM SEKOLAH PADA TOKO HANDAYANI BERBASIS WEB MOBILE (Information Technology and Telematics, 2014)
Abstract Along with the progress of time and the development of mobile technologies is rapidly increasing, the man in demand to follow the development of the technology itself. Sometimes men do not look at time in performing daily activities, they need something that is simple, one of which is the sale of school uniforms. In Stores Handayani own all activities regarding sales still done manually. Where to processing sales transactions, ordering and preparation of the report still takes a long time and is not efficient. So frequent occurrence that does not fit the data or even data loss occurs and many other cases. Final project entitled "School Uniform Sale In Stores Handayani Web- Mobile" aims to provide convenience for the customer in doing pemesana school uniform without having to come directly to get the school uniform. With web-based display of this mobile can also help the process of booking done. Keyword : Booking, Bus Tickets, Mobile Web